Trends and Challenges of Educational Administrators in Costa Rica: The Origin of a Project - Cerdas Montano, Virginia (2016)
This article investigates the underlying structural changes in school administration and curriculum that currently affects schools in both urban and rural settings including poorer, more marginalized communities. Upon analyzing each social context, it was perceived the aforementioned changes were closely associated with school administration practices dating back to the last ten years.  The article presents a general overview and methodological focus, a bibliographic review during the first and second stage of the project. The main conclusions refer to educational policies in Central America and the a questionnaire that is being developed  for teachers.